Implementasi Penegakan Hukum Lingkungan Hidup dalam Peraturan Pemerintah Nomor 26 Tahun 2023 Tentang Pengelolaan Hasil Sedimentasi di Laut - Murofikoh, Dede Ika; Pamula, Fauzi Rahmat (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2023)
Enforcement of environmental law is an act or process of coercion to comply with the law based on statutory regulations. One of the laws and regulations in which there are rules regarding environmental law enforcement is Government Regulation 26/2023 concerning the Management of Sedimentation Products at Sea. In enforcing environmental law, administrative sanctions alone are not enough, there must be civil and criminal sanctions, moreover, the damage and pollution done to the environment is quite severe and cannot be recovered. This study examines the lack of sanctions in the form of civil and criminal in Government Regulation 26/2023. Using normative research methods the authors find that in enforcing environmental law there must be civil sanctions, especially criminal ones, the use of criminal sanctions as a premium medium can be applied in enforcing environmental law if damage The damage caused is quite heavy and restoration of the damaged environment is difficult to do, especially sea sand which is a non-renewable natural resource discussed in Government Regulation 26/2023. Enforcement of environmental law is important to do for the continuity and welfare of human life and living things other.